Therapeutic potential of flavonoids in erosive tooth wear management: a scoping review - Nunes, Gabriel Pereira; de Oliveira Alves, Renata [UNESP]; Peres, Geórgia Rondó [UNESP]; de Toledo, Priscila Toninatto Alves; de Castilho, Aline Rogéria Freire (Springer Nature, 2025)
ObjectivesThis scoping review provides an overview of the use of flavonoids in managing erosive tooth wear, including preventive methods, therapeutic interventions, and strategies for its control.Materials and methodsThis scoping review was conducted in accordance with the PRISMA-ScR statement. A comprehensive search was conducted across multiple databases, retrieving all available records up to January 2025. Eligible evidence included in vivo, in vitro, and in situ studies investigating the therapeutic potential of flavonoids on erosive tooth wear. Data were extracted, and synthesis of study findings was performed.ResultsOf the 391 records screened, 34 studies were included in the review: two randomized clinical trials, 20 in vitro studies, five in situ investigations, and seven studies employing both in vitro and in situ approaches. Flavonoids demonstrated promising potential in the control of erosive tooth wear. Epigallocatechin-3-gallate (EGCG) was the most extensively studied and proved more effective than fluoride and chlorhexidine in dentin preservation, tissue loss reduction, and long-term adhesive performance. Proanthocyanidin also proved effective, especially in collagen stabilization and improved bond strength to eroded dentin. Quercetin stood out for its protective and reparative effects, including superior tubular occlusion, mechanical reinforcement, and preservation of the organic matrix. Although less investigated, theaflavin and hesperidin displayed dose-dependent effects in reducing wear and inhibiting matrix metalloproteinase activity.ConclusionsFlavonoids, especially EGCG, proanthocyanidin, and quercetin, show promising results in controlling erosive tooth wear, with multiple mechanisms including remineralization, anti-collagenolytic activity, and biomodification of dentin.Clinical relevanceFlavonoids may act as valuable adjunctive agents in preventive and restorative strategies for erosive tooth wear. However, further clinical trials are required to confirm their efficacy and establish optimal formulations for clinical application.